2022
DOI: 10.1177/00472875221127685
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Tourist Spatial and Temporal Patterns Using GPS and Sequence Alignment Method

Abstract: This study identified the spatial and temporal patterns of national park visitors by combining global positioning system (GPS) technologies and surveys using the sequence alignment method (SAM) based on the concept of space–time path of time geography. Data were collected from a sample of 344 GPS tracks and questionnaires obtained from Gyeryongsan National Park in South Korea. A complex random stratified sampling method was employed to represent a national sample based on mobile positioning data. The result of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
0
0
Order By: Relevance
“…What tourism sociologists conceptualized and anecdotally supported (e.g., [37]) can now be measured and analyzed. Information technology has enabled researchers to reconstruct visitor flows in a number of different ways: Geoand time-tagged data extracted from user-generated content on social media (e.g., [38,39]), from credit card transactions (e.g., [40]), from smartphones with their GPS locations [41][42][43][44], or captured from tourist cards (e.g., [45]). These data show that visitors are more likely to be at landmarks, attractions, and tourist sites than at other 'ordinary' places.…”
Section: Social Origin Of Destinationsmentioning
confidence: 99%
“…What tourism sociologists conceptualized and anecdotally supported (e.g., [37]) can now be measured and analyzed. Information technology has enabled researchers to reconstruct visitor flows in a number of different ways: Geoand time-tagged data extracted from user-generated content on social media (e.g., [38,39]), from credit card transactions (e.g., [40]), from smartphones with their GPS locations [41][42][43][44], or captured from tourist cards (e.g., [45]). These data show that visitors are more likely to be at landmarks, attractions, and tourist sites than at other 'ordinary' places.…”
Section: Social Origin Of Destinationsmentioning
confidence: 99%
“…Prior research concluded that recreation areas are commonly related to beneficial values such as enjoying nature, escaping from the noise, seeking solitude, and learning [29,35]. Bricker and Kerstetter [36] described that place meanings associated with recreational activities are the enjoyment/excitement of participating in an activity in a setting) and knowledge about the setting [37,38].…”
Section: Values Associated With Parksmentioning
confidence: 99%